Automated Insulin Delivery Around Exercise in Adults with Type 1 Diabetes: A Pilot Randomized Controlled Study - Olivia McCarthy (Diabetes Technology & Therapeutics, 2023)
Aim: To assess the effectiveness of an automated insulin delivery (AID) system around exercise in adults with type 1 diabetes (T1D). Methods: This was a three-period, randomized, crossover trial involving 10 adults with T1D (hemoglobin A1C; HbA1c: 8.3% ± 0.6% [67 ± 6 mmol/mol]) using an AID system (MiniMed 780G; Medtronic USA). Participants performed 45 min of moderate intensity continuous exercise 90 min after consuming a carbohydrate-based meal using three strategies: (1) a 100% dose of bolus insulin with exercise announcement immediately at exercise onset “spontaneous exercise” (SE) or a 25% reduced dose of bolus insulin with exercise announcement either (2) 90 min (AE90) or (3) 45 min (AE45) before exercise. Venous-derived plasma glucose (PG) taken in 5 and 15 min intervals over a 3 h collection period was stratified into the percentage of time spent below (TBR [<3.9 mmol/L]), time in range (TIR [3.9–10 mmol/L]), and time above range (TAR [ > 10 mmol/L]). In instances of hypoglycemia, PG data were carried forward for the remainder of the visit. Results: Overall, TBR was greatest during SE (SE: 22.9 ± 22.2, AE90: 1.1 ± 1.9, AE45: 7.8% ± 10.3%, P = 0.029). Hypoglycemia during exercise occurred in four participants in SE but one in both AE90 and AE45 (ꭓ2 [2] = 3.600, P = 0.165). In the 1 h postexercise period, AE90 was associated with higher TIR (SE: 43.8 ± 49.6, AE90: 97.9 ± 5.9, AE45: 66.7% ± 34.5%, P = 0.033), lower TBR (SE: 56.3 ± 49.6, AE90: 2.1 ± 5.9, AE45: 29.2% ± 36.5%, P = 0.041) with the greatest source of discrepancy observed relative to SE. Conclusion: In adults using an AID system and undertaking postprandial exercise, a strategy involving both bolus insulin dose reduction and exercise announcement 90 min before commencing the activity may be most effective in minimizing dysglycemia. The study was registered as a clinical trial (Clinical Trials Register; NCT05134025).